Advanced glycation end product deposits in climatic droplet keratopathy. Issue 1 (14th September 2006) - Kaji, Y; Nagai, R; Amano, S; Takazawa, Y; Fukayama, M; Oshika, T
Abstract : Background: Climatic droplet keratopathy (CDK), known as spheroid degeneration of the cornea, is one of the most frequent degenerative corneal disorders affecting visual function. However, the histochemical nature of the deposits seen in CDK is still unclear. Aim: To investigate the pathogenesis of CDK, we investigated the immunohistochemical localisation of advanced glycation end products (AGEs) in surgical specimens of CDK. Methods: Immunohistochemical localisation of N ε -(carboxymethyl)-l -lysine (CML), N ε -(carboxyethyl)-l -lysine (CEL), pyrraline, pentosidine and imidazolone was examined in three corneas with CDK, six corneas with bullous keratopathy and three corneas without any corneal diseases. Results: In all the specimens with CDK, immunoreactivity was strong in CML, moderate in pyrraline and pentosidine, and weak in imidazolone. Immunoreactivity was absent in CEL. In contrast, no immunoreactivity to CML, pyrraline, pentosidine, imidazolone or CEL was detected in corneas with bullous keratopathy, or in corneas without any corneal diseases. Conclusions: CDK is caused by an aggregation of AGE-modified proteins. The result is consistent with etiological findings that ultraviolet irradiation and ageing, both of which are accelerators of AGE formation, are closely related to the development of CDK.